Communities of Practice (CoP) Sharing Session on Resilience - Amalia, Madihie (2016)
Presented to the Sarawak Communities of Practice (CoP) as part of sharing sessions with professionals on resilience at Wisma Bapa Malaysia, Kuching, Sarawak Malaysia.